Comparison of earthquake behavior of buildings using different structural materials - Ean, Yong-ho; Wireland, Martin; Worsak Kanok-Nukulchai; Umita, Teruyuki; Government of Republic of China (Bangkok : Asian Institute of Technology, 1983)
The study of the seismic behavior of three different building materials, viz., normal weight concrete, lightweight concrete and steel, is presented. Three existing normal weight concrete buildings from Taiwan are chosen for the analysis. The buildings are modelled as two-dimensional moment-resistant frames fixed to the rigid foundation. Static and dynamic loadings are considered simultaneously. Corresponding lightweight concrete and steel buildings, designed on the basis of similar strength characteristics in accordance with the ACI and AISC codes, serve as comparative structures. An artificial acceleration time history based on a smoothed response spectrum of Taiwanese earthquakes is used as dynamic loading. The nonlinear analysis is carried out using the DRAIN-2D computer program. In all, three sets of each material of 3, 5 and 10 story buildings are analyzed. From the dynamic analysis the maximum values of the response are obtained plus information regarding the inelastic behavior of structural elements. Results show that while lightweight and normal weight concrete exhibit similar dynamic behavior with the formation of plastic hinges in certain elements, the steel structure continues to remain elastic. Therefore, it can be concluded that steel structures possess excellent seismic resistance and it appears that steel is the most suitable structural material in regions of high seismicity.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Earthquakes and building; Building materials -- Research